Diaphragm and preparation method thereof

By adopting a composite structure of modified COFs materials and inorganic particles in the lithium secondary battery separator, the shortcomings in the existing separator in terms of mechanical properties and ion conductivity are solved, higher wettability and ion conductivity are achieved, battery polarization is reduced, and the process is feasible.

CN119921056AActive Publication Date: 2025-05-02CHONGQING TALENT NEW ENERGY CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411690091.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2025-05-02
Estimated Expiration
2044-11-25

AI Technical Summary

Technical Problem

The existing COFs-based lithium secondary battery separators have limitations in terms of mechanical properties and usage scenarios, and the self-assembly process depends on laboratory-level control, making it difficult to achieve industrial control. At the same time, the existing composite separators have shortcomings in improving ion conduction efficiency, and the polarity of the polyolefin substrate film layer is low, which affects the wetting properties of the electrolyte.

Method used

A composite separator structure is adopted, including a substrate film layer and a modified layer, which consists of a modified COFs material and inorganic particles. The modified COFs material is formed by applying groups containing active hydrogen and substituting them with lithium ions, and the modified layer is formed by coating process, which improves the wettability and ionic conductivity of the separator by utilizing the lyophilicity of the inorganic particles and the high specific surface area of ​​the COFs material.

Benefits of technology

Through the synergistic effect of modified COFs materials and inorganic particles, the wetting and ion conductivity of the separator are significantly improved, the polarization phenomenon of the battery is reduced, and this process can realize industrial manipulation, improving the heat resistance and processability of the separator.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119921056A_ABST
    Figure CN119921056A_ABST
Patent Text Reader

Abstract

The invention mainly provides a composite diaphragm for a secondary battery and a preparation method of the composite diaphragm. The composite diaphragm comprises a base material layer and a modified layer formed on at least one surface of the base material layer, wherein the base material layer comprises a high polymer material; the modified layer comprises a modified covalent organic framework material and inorganic particles, the molecular structure of the modified covalent organic framework material has groups containing active hydrogen, hydrogen ions in the groups containing the active hydrogen can be replaced by lithium ions, and in addition, the hydrogen ions in the groups containing the active hydrogen can be replaced by lithium ions. Hydrogen ions in at least part of the groups containing active hydrogen are replaced by lithium ions.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of new energy, and specifically relates to a diaphragm that can be used for lithium secondary batteries, in particular to a composite battery diaphragm based on an organic-inorganic hybrid system and a preparation method thereof. Background Art

[0002] Covalent organic frameworks (COFs) compounds are a class of two-dimensional or three-dimensional structural materials formed by reactions between organic precursors. They have strong covalent bonds, thus providing many excellent physical and chemical properties such as special porosity, excellent electrical conductivity, high stability and good crystallinity.

[0003] As a new type of crystalline porous polymer, covalent organic framework materials have broad application prospects in the fields of adsorption, catalysis, environment and energy. In the past decade, with the continuous deepening of research, COFs materials with different topological structures have been gradually developed. Most of the COFs materials reported so far have a two-dimensional (2D) extended structure. For example, these 2D-COFs materials are basically extended from triangles, quadrilaterals, and hexagonal structures.

[0004] The application of covalent organic frameworks in lithium secondary batteries, especially solid-state batteries, has also been developed to a certain extent. They have been applied to a certain extent in electrode materials, solid-state electrolyte materials and separators.

[0005] Furthermore, lithium battery separators currently generally use coating technologies such as micro-gravure, spraying, and spot coating to improve the performance of lithium batteries and improve battery interface problems.

[0006] Some studies have reported that COFs materials are modified by epoxy, PEG, etc., and then mixed with lithium salts to form solid electrolyte membranes. However, such electrolyte membranes usually have insufficient self-support and mechanical properties. The existing COFs-based membrane coatings are mainly filtered by vacuum self-assembly to obtain flexible self-supporting membranes. For example, some studies have reported a flexible self-supporting membrane composited with a covalent organic framework material and bacterial cellulose. After the covalent organic framework material and bacterial cellulose are mixed in an aqueous solution, they are filtered onto a microporous filter membrane, and then peeled off after drying to obtain a covalent organic framework self-supporting membrane.

[0007] In addition, in other cases, it has been proposed to use modified COFs materials mixed with polar adhesive components in a strong polar solvent, and then self-assemble on the surface of an organic membrane by suction filtration to obtain a composite membrane. Summary of the invention

[0008] Problem that the invention aims to solve

[0009] As mentioned above, some of the current COFs-based membranes are used in the form of electrolyte membranes, which have certain limitations in mechanical properties and usage scenarios. In addition, the processing method of using COFs and other organic components to form self-support or organic membranes mainly relies on self-assembly methods such as filtration, which is mainly based on the dispersion of COFs in the mixed system. This self-assembly method currently relies mostly on laboratory-level control methods, which is different from the conventional coating method for preparing membranes in terms of convenience and industrial controllability.

[0010] In addition, in the current preparation of composite membranes with coatings, a layer containing inorganic particles is usually formed on one or both sides of a polyolefin substrate membrane layer. However, although this structure can improve the thermal stability of the entire membrane, it cannot essentially provide faster or higher ion conduction efficiency. In addition, the polyolefin substrate membrane layer in these composite membranes cannot be said to be completely ideal in terms of electrolyte wettability due to its low polarity.

[0011] In view of the above problems, the present invention mainly provides a composite separator for a lithium secondary battery, which includes a substrate film layer and a modified layer formed on at least one surface of the substrate, wherein the modified layer includes a modified COFs material and inorganic particles.

[0012] In this structure, the modified layer can improve the wettability of the entire diaphragm to the electrolyte. This is because inorganic materials (such as ceramic materials, etc.) are lyophilic, and the modified (two-dimensional) COFs material has a large specific surface area and can store a large amount of electrolyte. The ceramic and COFs materials work together to improve the overall wettability of the diaphragm. In addition, lithium ions are given to the modified COFs material, and the lithium ions will dissociate from the COFs skeleton, play a role in transmitting lithium ions, and improve the ionic conductivity of the diaphragm; at the same time, during the operation of the high-rate battery, the dissociated lithium ions in the diaphragm modified layer can regulate the lithium ion concentration in the electrolyte, uniform the electric field, regulate the lithium ion flux, and reduce the polarization of the battery as much as possible.

[0013] In addition, it was also found that when the modified COFs material is mixed with inorganic particles, the (two-dimensional) modified COFs material can be well dispersed in the water system with the help of inorganic particles due to its surface properties, and thus, it is not necessary to rely on the self-assembly mentioned above, but only conventional coating methods are needed to efficiently form a modified layer.

[0014] Therefore, in general, the composite separator provided by the present invention achieves improved performance of lithium batteries by leveraging the synergistic effect of inorganic particles and COFs materials.

[0015] Solutions for solving problems

[0016] Through long-term practice, it is found that the above technical problems can be solved by implementing the following technical solutions:

[0017] The present invention first provides a composite diaphragm for a secondary battery, wherein the composite diaphragm comprises:

[0018] A substrate layer, and a modified layer formed on at least one surface of the substrate layer;

[0019] in,

[0020] The substrate layer includes a polymer material;

[0021] The modified layer includes modified covalent organic framework materials and inorganic particles.

[0022] The modified covalent organic framework material has a group containing active hydrogen in its molecular structure.

[0023] The hydrogen ions in the groups containing active hydrogen can be replaced by lithium ions, and at least part of the hydrogen ions in the groups containing active hydrogen are replaced by lithium ions.

[0024] According to the composite diaphragm of the present invention, the modified layers are present on both surfaces of the substrate layer, and the two modified layers are the same or different.

[0025] According to the composite separator of the present invention, the substrate layer comprises a polyolefin resin; and the thickness of the modified layer is 5 μm or less.

[0026] According to the composite separator of the present invention, the substrate layer is a polyolefin porous membrane layer.

[0027] According to the composite diaphragm of the present invention, wherein in the modified layer, the mass ratio of the modified covalent organic framework material to the inorganic particles is 3:7 to 7:3.

[0028] According to the composite diaphragm of the present invention, the group containing active hydrogen includes one or more of a carboxyl group, a phosphoric acid group, a sulfonic acid group, and a phenolic hydroxyl group.

[0029] According to the composite separator of the present invention, substantially all hydrogen ions in the active hydrogen-containing groups are replaced by lithium ions.

[0030] Furthermore, the present invention also provides a method for preparing the composite diaphragm according to the above, wherein the method comprises:

[0031] A step of modifying the covalent organic framework material to impart active hydrogen-containing groups to the molecules of the covalent organic framework material, and then causing the hydrogen ions in the active hydrogen-containing groups to be at least partially replaced by lithium ions to obtain the modified covalent organic framework material;

[0032] A mixing step of dispersing and mixing the modified covalent organic framework material and the inorganic particles in water to obtain a mixed slurry;

[0033] The step of forming the modified layer comprises applying the mixed slurry to at least one surface of the substrate layer.

[0034] According to the above method, in the mixing step, the dispersing mixing is carried out in the presence of a binder, and optionally, a processing aid may also be used.

[0035] According to the above method, in the step of forming the modified layer, the coating includes roller coating, blade coating, spot coating or spray coating.

[0036] Effects of the Invention

[0037] By implementing the above technical solution, the present invention can achieve the following technical effects:

[0038] 1) By using modified COFs materials and inorganic particles (ceramic materials), not only can the overall wettability of the diaphragm be increased, but also the overall ionic conductivity of the membrane can be greatly improved;

[0039] 2) Since the modified COFs material contains electrostatically interacting lithium ions in the molecules, it can regulate the lithium ion concentration in the electrolyte / electrolyte, uniform the electric field and regulate the ion flux when the battery operates at a high rate (such as 5C, 6C, or even 10C). Therefore, it can reduce the polarization phenomenon near the battery separator interface.

[0040] 3) In the modified layer, the modified COFs are used in combination with inorganic particles, which not only improves the heat resistance of the entire membrane but also improves the ionic conductivity. At the same time, the above-mentioned composite use can provide better processability. That is, since the mixed slurry formed by the modified COFs and inorganic particles has good dispersibility, it is possible to obtain the modified layer of the present invention by coating processing without the need for self-assembly processes such as filtration. BRIEF DESCRIPTION OF THE DRAWINGS

[0041] Figure 1 : Schematic diagram of the structures of various modified COFs materials that can be used in the present invention, wherein R: acetate, sulfonate, phosphate, phenolic hydroxyl salt. DETAILED DESCRIPTION

[0042] The following is a detailed description of the present invention. The following description of the technical features is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0043] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0044] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0045] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0046] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0047] In this specification, the "normal temperature" or "room temperature" used means an indoor ambient temperature of "23±2°C".

[0048] In this specification, the unit names used are all international standard unit names, and unless otherwise stated, the "%" used indicates weight or mass percentage.

[0049] In the present specification, the use of “substantially” or “essentially” means that the standard deviation from a theoretical model, theoretical data or target data is within a numerical range of 1%, preferably 0.8%, and more preferably 0.5%.

[0050] In this specification, when the terms “include” and / or “comprise” are used, they indicate the existence of features, steps, operations, devices, components and / or their combinations.

[0051] In this specification, the references to "some specific / preferred embodiments", "other specific / preferred embodiments", "embodiments", etc., mean that the specific elements (e.g., features, structures, properties and / or characteristics) described in connection with the embodiments are included in at least one embodiment described herein, and may or may not exist in other embodiments. In addition, it should be understood that the elements may be combined in various embodiments in any suitable manner.

[0052] The present invention mainly provides a secondary battery separator having a composite structure, wherein the composite separator has a substrate layer and a modified layer formed on at least one surface of the substrate layer. The present invention is mainly based on the following insights:

[0053] Although COFs materials have been used in the preparation of secondary battery separators due to their excellent ion conductivity and other properties, their (super) hydrophobic surface properties make it difficult to modify them or mix them with other components. For example, self-supporting or supported membranes based on COFs materials usually require self-assembly processes such as filtration. The present invention has found that when modified COFs are mixed with inorganic particles, good dispersibility can be obtained even in an aqueous dispersion system, and as a result, a composite separator can be obtained by conventional coating means. In addition, due to the synergistic effect of the modified COFs and inorganic particles, the separator not only improves the wettability of the separator as a whole to the secondary battery electrolyte / liquid, but also has improved thermal stability and improved ion transmission capacity.

[0054] <First aspect>

[0055] In a first aspect of the present invention, a composite separator for a secondary battery is provided, wherein the separator comprises a substrate layer and a modified layer formed on at least one surface of the substrate layer.

[0056] (Covalent organic framework materials-COFs materials)

[0057] Covalent organic framework compounds are a type of two-dimensional or three-dimensional structural materials formed by reactions between organic precursors. In the art, they exist more in a two-dimensional form. Therefore, the present invention preferably uses two-dimensional COFs materials.

[0058] The COFs material that can be used in the present invention may have a structural form expanded from a triangular, quadrilateral, or hexagonal structure.

[0059] Furthermore, in principle, there is no particular limitation on the synthesis method of the COFs material of the present invention, and the COFs material can be obtained according to conventional synthesis methods in the art.

[0060] In some specific embodiments, the above-mentioned synthesis method includes coupling reaction, nucleophilic addition-elimination reaction, condensation reaction, etc. In some preferred embodiments of the present invention, the synthesis method can be coupling reaction or nucleophilic addition-elimination reaction, and more preferably, it can be obtained based on nucleophilic addition-elimination reaction.

[0061] In principle, there is no particular limitation on the reactants for the nucleophilic addition-elimination reaction. For example, conventional polyamines and polyaldehydes in the art may be used for the reaction.

[0062] In some specific embodiments, the polyamine and polyaldehyde are compounds with a functionality of 2 or more, and at least one of them has a functionality greater than 2. In addition, in some preferred embodiments, at least two of the amines in the polyamine are primary amines, or all of them are primary amines.

[0063] Further, in some specific embodiments, the polyamine can be a 2-5-membered amine, for example, a diamine, a triamine, a tetraamine or a pentaamine; the polyaldehyde can be a 2-5-membered aldehyde, for example, a dialdehyde, a trialdehyde, a tetraaldehyde or a pentaaldehyde.

[0064] In some preferred embodiments, the polyamine is a 3- to 5-membered amine, or the polyaldehyde is a 3- to 5-membered aldehyde.

[0065] For the polyamine and polyaldehyde, preferably, at least one of them has an aromatic structure, and more preferably, both of them have an aromatic structure.

[0066] For the above aromatic structure, in some specific embodiments, it can be an aromatic ring with 4 to 16 ring atoms, preferably an aromatic ring with 5 to 10 ring atoms, such as a benzene ring. Such a ring can include a single ring or a condensed ring.

[0067] Furthermore, the aromatic ring may be a carbon aromatic ring or a heteroaromatic ring containing a heteroatom. Such a heteroatom is not particularly limited and may be, for example, an O, N or S atom.

[0068] In addition, the polyamine or polyaldehyde may have one or more of the above-mentioned aromatic rings in its structure. Preferably, these aromatic rings may be connected via a single bond or an optional multivalent organic group.

[0069] The polyamines that can be cited in the present invention may include, in some specific embodiments:

[0070]

[0071] Wherein, A represents -NH2 or -CO-NH-NH2 group.

[0072] n represents an integer of 2 to 4, and m is usually 1 or 2, preferably 1.

[0073] The polyaldehydes that can be listed in the present invention may include, in some specific embodiments:

[0074]

[0075] Wherein, B represents a -CHO group.

[0076] p represents an integer of 2 to 4; q may generally be 1 or 2, preferably 1.

[0077] Furthermore, the aromatic structure (aromatic ring) of the present invention may optionally be connected to other groups in addition to groups such as A or B.

[0078] In principle, there is no particular limitation on such other groups, and they include, for example, halogen groups, halogenated hydrocarbon groups, saturated or unsaturated aliphatic hydrocarbon groups, (poly)ether-containing groups, and the like.

[0079] In addition, in some specific embodiments, the other groups are preferably groups containing active hydrogen. Such groups can generally include one or more of carboxyl, phosphate, sulfonate, hydroxyl, thiol, etc., preferably one or more of carboxyl, phosphate, sulfonate or phenolic hydroxyl.

[0080] Therefore, in some specific embodiments of the present invention, the active hydrogen-containing groups in the COFs material can be introduced via raw material monomers during the synthesis of the COFs material.

[0081] Furthermore, in principle, there is no particular limitation on the synthesis method of the COFs material, which can be carried out according to existing methods in the art.

[0082] (Modified COFs materials)

[0083] The modified COFs material of the present invention mainly refers to replacing the active hydrogen in the groups containing active hydrogen in the COFs material molecules with lithium ions. As mentioned above, such groups containing active hydrogen can generally include one or more of carboxyl, phosphoric acid, sulfonic acid, hydroxyl, thiol, etc., preferably one or more of carboxyl, phosphoric acid, sulfonic acid or phenolic hydroxyl.

[0084] Further, two cases are included according to the source of the group containing active hydrogen:

[0085] Case 1: As mentioned above, if one or both of the polyamines or polyaldehydes already have active hydrogen-containing groups in the molecules when synthesizing the COFs material, the obtained COFs material directly has active hydrogen-containing groups. At this time, the COFs material can be directly subjected to subsequent lithium ion replacement;

[0086] Case 2: If neither the polyamine nor the polyaldehyde has a group containing active hydrogen in its molecule when synthesizing the COFs material, the COFs material is further treated after synthesis to impart a group containing active hydrogen in its molecular structure.

[0087] In principle, there is no particular limitation on further treatment in case 2. For example, active hydrogen-containing groups can be further introduced into the COFs molecular structure by means of coupling reaction, addition reaction, grafting reaction, etc.

[0088] In the present invention, both the above-mentioned situation 1 and situation 2 can be referred to as imparting a group containing active hydrogen to the covalent organic framework material molecule.

[0089] Furthermore, the above replacement can be performed under alkaline conditions. In some specific embodiments, COFs can be treated with a solution containing lithium salts and / or LiOH.

[0090] A specific modified COFs molecular structure can be specifically listed, see the present invention Figure 1 , whose "R" groups are treated with alkaline conditions to obtain various types of lithium-containing salts.

[0091] Through the above-mentioned replacement treatment, the hydrogen ions in the groups containing active hydrogen in the COFs material can be at least partially replaced, and further, these hydrogen ions can be substantially completely replaced by lithium ions.

[0092] (Composite diaphragm)

[0093] The composite diaphragm of the present invention mainly comprises a substrate layer and a modified layer containing the modified COFs material and inorganic particles.

[0094] Base material layer

[0095] In principle, there is no particular limitation on the substrate layer of the present invention, and it may be a porous membrane layer commonly used in secondary batteries, especially lithium secondary batteries.

[0096] For such a porous membrane, preferably, various polymer material-based porous membranes can be used, and these polymers include various artificial polymers and natural polymers. In some specific embodiments, the porous membrane is formed by a composition including a polyolefin resin or a cellulose material composition. More preferably, the porous membrane can be formed by a polyolefin material.

[0097] The polyolefin material mentioned above may be formed by homopolymerization or copolymerization of monounsaturated olefin monomers having 2 to 8 carbon atoms. In some preferred embodiments, the olefin monomers may be ethylene, propylene, styrene, butylene, etc. More preferably, the porous membrane of the present invention may be made of

[0098] The film is formed of a resin material including polyethylene or polypropylene, or is formed of polyethylene or polypropylene.

[0099] The porosity of the substrate layer of the present invention is not particularly limited, and may be, for example, 20 to 45 v%, preferably 25 to 42 v%.

[0100] In principle, there is no particular limitation on the thickness of the substrate layer. The thickness may be 20 μm or less, for example, 5 to 10 μm.

[0101] Modified layer

[0102] The modified layer of the present invention is mainly obtained by mixing the modified COFs material and inorganic particles to obtain a system suitable for coating.

[0103] Traditional COFs materials usually have high hydrophobicity and their own surface morphology characteristics, which makes them less dispersible.

[0104] The present invention has found that when the modified COFs material and inorganic particles are mixed, a mixed system with good dispersibility can be obtained even with only an aqueous solvent or even with water as a solvent. It is speculated that this may be related to the lithium ions given to the modified COFs material, or it may be related to the adsorption of the modified COFs material and its interaction with the inorganic particles.

[0105] Further, in some specific embodiments of the present invention, the modified COFs material and the inorganic particles can be mixed in water. Optionally, a binder and other processing aids can be used when necessary.

[0106] For the inorganic particles of the present invention, various ceramic particles commonly used in battery separators in the art can be used. In some preferred embodiments of the present invention, the ceramic can be selected from at least one of boehmite, aluminum oxide, magnesium hydroxide, magnesium oxide, titanium dioxide, silicon dioxide, titanium oxide, barium titanate, zinc oxide, nickel oxide, magnesium fluoride, zirconium oxide, cerium oxide, and barium sulfate. There is no particular restriction on the particle size of such particles, and their Dv50 can generally be 0.5 to 2 μm, preferably 0.7 to 1.5 μm.

[0107] The ratio of the modified COFs material to the inorganic particles can generally be 3:7 to 7:3, preferably 5:5 to 7:3, from the perspective of dispersibility, heat resistance and ion conductivity.

[0108] In principle, there is no particular limitation on the above-mentioned adhesive, and examples thereof include fluorinated olefin adhesives, such as COPNA resin adhesives, PVDF adhesives, and the like.

[0109] In principle, there is no particular limitation on the processing aids mentioned above, and examples thereof include dispersants, thickeners, wetting agents, etc. In some specific embodiments, the dispersant includes a hydrolyzed polymaleic anhydride dispersant; the thickener includes a sodium carboxymethyl cellulose thickener; and the wetting agent includes a silanol nonionic surfactant wetting agent.

[0110] In addition, in the mixed system, the total content of the modified COFs material and the inorganic particles may be 94% by mass or more, preferably 94% by mass to 96% by mass, calculated as solid matter or dry matter.

[0111] By the above mixing, a slurry containing the modified COFs material and the inorganic particles can be obtained. Furthermore, the slurry is applied to the above substrate layer to form a modified layer and obtain the composite separator of the present invention.

[0112] There is no particular limitation on the coating method, and the coating may be performed by roller coating, scraper coating, spot coating or spray coating according to the specific solid content and viscosity of the slurry. More specifically, a slurry liquid is obtained, and then the slurry liquid is coated on the surface of the diaphragm by micro-gravure / gravure roller coating, spray coating or spot coating.

[0113] In principle, there is no particular limitation on the thickness of the modified layer in the final composite diaphragm, which can usually be less than 5 μm, for example, 0.1 to 4.5 μm, preferably 1.5 to 4 μm, including 0.5 μm, 1.0 μm, 1.8 μm, 2.2 μm, 2.5 μm, 3.0 μm, 3.5 μm, etc.

[0114] In the present invention, firstly, the use of a coating containing inorganic particles in the composite diaphragm can increase the thermal stability of the diaphragm; secondly, the coating also improves the wettability of the diaphragm to the electrolyte, because LiOH or lithium salt is used to replace the active hydrogen ions in the COFs molecules with Li through lithium ion exchange, thus becoming a new type of ion conductor. At the same time, relying on the large specific surface area of ​​the COFs material, a large amount of electrolyte can be stored. The lithium ions in structures such as lithium sulfonate and lithium carboxylate existing on the surface of the covalent organic framework material will dissociate from the COFs skeleton, play a role in transmitting lithium ions, and improve the ionic conductivity of the diaphragm; at the same time, during the operation of the high-rate battery, the dissociated lithium ions in the diaphragm modified layer can regulate the lithium ion concentration in the electrolyte, uniform the electric field, regulate the lithium ion flux, and reduce the polarization of the battery as much as possible. By giving play to the synergistic effect of inorganic particles and modified COFs materials, the performance of the secondary battery is improved.

[0115] (Secondary battery)

[0116] The secondary battery described in the present invention includes various secondary batteries with ion conduction, and in particular, refers to lithium secondary batteries, including non-aqueous electrolyte lithium secondary batteries, semi-solid, quasi-solid lithium secondary batteries, etc.

[0117] The secondary battery of the present invention may be a power battery, that is, a battery used to provide power for transportation or vehicles, or a secondary battery used in energy storage equipment such as wind power, hydropower, solar power or traditional petrochemical energy power.

[0118] In some specific embodiments, the battery of the present invention appears and is used in a single form. In other specific embodiments, the battery of the present invention can be used in parallel or in series in any number of scales.

[0119] The lithium secondary battery of the present invention may include a positive electrode, a negative electrode, an electrolyte and the composite separator.

[0120] The positive electrode includes a current collector and a positive electrode active material and optionally used additives, etc. In principle, there is no particular limitation on the positive electrode active material, for example, it can be a lithium oxide doped with a transition metal, typically, it can be a ternary lithium positive electrode active material doped with nickel, manganese, and cobalt.

[0121] The negative electrode may include a current collector, a negative electrode active material, and optional auxiliary agents, etc. The negative electrode active material may include carbon-based materials and non-carbon-based materials.

[0122] The carbon-based materials include graphite materials (natural graphite, artificial graphite and intermediate carbon spheres) and other carbon-based materials (hard carbon, soft carbon and graphene); the non-carbon-based materials can be subdivided into titanium-based materials, silicon-based materials, tin-based materials, nitrides and metallic lithium, etc.

[0123] Furthermore, in principle, there is no particular limitation on the electrolyte solution that can be used in the secondary battery of the present invention.

[0124] In some specific embodiments, the electrolyte comprises an electrolyte and a non-aqueous solvent.

[0125] The present invention does not particularly limit the type of the non-aqueous solvent, as long as it is a non-aqueous solvent commonly used as a non-aqueous electrolyte solution.

[0126] In some specific embodiments, the non-aqueous solvent can be selected from one or more of cyclic carbonate solvents, linear carbonate solvents, ether solvents, ester solvents, and ketone solvents.

[0127] The cyclic carbonate solvent can be selected from ethylene carbonate (EC), propylene carbonate (PC), and butylene carbonate (BC); the linear carbonate solvent can be selected from diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC), methyl trifluoroethyl carbonate (FEMC), di(2,2,2-trifluoroethyl) carbonate (DFDEC), etc. The ester solvent can be selected from methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, methyl butyrate, ethyl butyrate, and methyl pivalate, etc.; the ether solvent can be selected from dibutyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, 1,2-dimethoxyethane, ethylene glycol dimethyl ether (DME), ethylene glycol diethyl ether (DEE), dioxane (DX), dioxolane (DOL), etc.; the ketone solvent can be selected from polymethyl vinyl ketone, etc. These non-aqueous solvents can be used alone or in the form of a mixture of two or more.

[0128] In some preferred embodiments, the non-aqueous solvent can be selected from one or more of ethylene carbonate (EC), propylene carbonate (PC), dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), ethyl acetate, propyl acetate, ethyl propionate, propyl ester, methyl butyrate, and ethyl butyrate.

[0129] The electrolyte of the present invention can generally be various lithium salts. The present invention does not specifically limit the type of lithium salt, and can be a lithium salt commonly used in the art. In some specific embodiments, the lithium salt can be selected from one or more salts formed by lithium ions and the following anions: PF6 - 、BF4 - , Cl - Br - ,I - 、ClO4 - 、AsF6 - 、SiF6 2- 、AlCl4 - 、B(C2O4)2 - 、CH3CO2 - CF3SO3 - 、N(CF3SO2)2 - 、N(FSO2)2 - 、C(CF2SO2)3 - 、C2BF2O4 - .

[0130] In principle, there is no particular limitation on other functional additives that can be used in the electrolyte of the present invention. For example, the use of some additives can promote film formation.

[0131] For such additives, examples include vinyl ethylene carbonate (VC), lithium difluorophosphate (LiPO2F2), fluoroethylene carbonate (FEC), boron-containing additives, sulfur-containing additives or oxalate-containing additives, etc. Among them, the boron-containing additive can be selected from lithium tetrafluoroborate (LiBF4), trimethylsilyl phosphate (TMSP), trimethylsilyl borate (TMSB), etc.; the sulfur-containing additive can be selected from 1,3-propane sultone (1,3PS), 1,4-butane sultone (1,4-BS), 2,4-butane sultone (2,4-BS), 1,3-propylene sultone (PST), vinyl sulfate (DTD), methylene disulfonate (MMDS), vinyl sulfite (ES), etc.; the oxalate-containing additive can be selected from lithium difluorooxalatoborate (LiDFOB), lithium bisoxalatoborate (LiBOB), lithium tetrafluorooxalatophosphate (LiTFOP), lithium difluorobisoxalatophosphate (LiDFOP), etc. These additives may be used alone or in admixture of two or more.

[0132] In summary, in the secondary battery of the present invention, due to the design of the structure of the modified layer formed by inorganic particles and modified COFs, the effects of high heat resistance, high wettability, high liquid absorption rate, high mechanical strength and high ionic conductivity of the composite diaphragm are achieved. The inorganic particles are mixed with the modified COFs material, not only the lyophilicity of the inorganic particles / ceramics greatly improves the wettability of the electrolyte to the diaphragm, but also the slurry obtained by mixing the two has good uniform dispersion, so that the wettability of the modified COFs material to the electrolyte is greatly improved, and therefore, the larger specific surface area of ​​COFs can be fully utilized to store a large amount of electrolyte. And the lithium ions given to the modified COFs material will dissociate from the COFs skeleton, play the role of transmitting lithium ions, and improve the ionic conductivity of the diaphragm. In addition, during the operation of the high-rate battery, the dissociated lithium ions in the diaphragm modified layer can regulate the lithium ion concentration in the electrolyte, uniform electric field, regulate lithium ion flux, and reduce the polarization of the battery as much as possible.

[0133] Example

[0134] The embodiments of the present invention will be described in detail below in conjunction with the examples, but those skilled in the art will appreciate that the following examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. If no specific conditions are specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0135] raw materials :

[0136] Modified COFs materials: The modified COFs materials used in the examples of the present invention and comparative examples 1-3 are as follows Figure 1 The structure shows that in Comparative Example 3, R is replaced by a sulfonic acid group.

[0137] Comparative Example 4 is a COFs material formed by m-dialdehyde toluene and 4,4'-diaminobiphenyl.

[0138] Thermal Shrinkage Test Method :

[0139] Cut the coated diaphragm into 10cm×10cm pieces, clamp them with A4 paper, and heat them in a 200℃ forced air oven for 1 hour. After the test is completed, use a steel ruler to measure the length in the TD and MD directions, and calculate the thermal shrinkage rate based on the shrinkage length. The thermal shrinkage rate calculation formula of the diaphragm is:

[0140] Thermal shrinkage rate (%) = (Li-Lf) / Li*100%, Li is the size before the test, and Lf is the size after the test.

[0141] Ionic conductivity test method :

[0142] By assembling symmetrical batteries with 1, 2, and 3 layers of diaphragm, a linear curve was fitted according to the measured impedance of the diaphragm. The slope k is the diaphragm resistance. The ionic conductivity was calculated according to the formula σ=0.1d / (Rs*A), where d is the thickness (μm) and Rs is the diaphragm resistance (Ω), and the value of ionic conductivity was obtained.

[0143] Example 1 :

[0144] The ceramic particles and modified COFs materials are evenly dispersed in water, and the mass ratio of ceramic to modified COFs materials is 45%:55%. The solid and additive ratios are 95% and 5% respectively (dispersant accounts for 0.4%, binder accounts for 4%, thickener accounts for 0.5%, and wetting agent accounts for 0.1%). The mixed slurry is evenly coated on the PE base film by micro-gravure roller coating, and the coating thickness is 3um. Heated at 200℃ for 1h, the thermal shrinkage ratio of the diaphragm TD<2.3, MD<2.5. The lithium ion conductivity is 1.83mS / cm, and the membrane breaking temperature is 210℃.

[0145] Example 2 :

[0146] The ceramic particles and modified COFs materials are evenly dispersed in water, and the mass ratio of ceramic to modified COFs materials is 35%:65%. The solid and additive ratios are 95% and 5% respectively (dispersant accounts for 0.4%, binder accounts for 4%, thickener accounts for 0.5%, and wetting agent accounts for 0.1%). The mixed slurry is evenly coated on the PE base film by micro-gravure roller coating, and the coating thickness is 3um. Heated at 200℃ for 1h, the thermal shrinkage ratio of the diaphragm TD<3.0, MD<3.0. The lithium ion conductivity is 1.24mS / cm, and the membrane rupture temperature is 205℃.

[0147] Example 3 :

[0148] The ceramic particles and modified COFs materials are evenly dispersed in water, and the mass ratio of ceramic to modified COFs materials is 65%:35%. The solid and additive ratios are 95% and 5% respectively (dispersant accounts for 0.4%, binder accounts for 4%, thickener accounts for 0.5%, and wetting agent accounts for 0.1%). The mixed slurry is evenly coated on the PE base film by micro-gravure roller coating, and the coating thickness is 3um. Heated at 200℃ for 1h, the thermal shrinkage ratio of the diaphragm TD<2.5, MD<2.8. The lithium ion conductivity is 1.32mS / cm, and the membrane breaking temperature is 208℃.

[0149] Example 4 :

[0150] Except that the lithium sulfonate group in the modified COFs material is replaced by a lithium phosphate group (modified COFs-1), the rest is the same as Example 1. The mass ratio of ceramic to modified COFs-1 material is 45%:55%. The solid and additive account for 95% and 5% respectively (dispersant accounts for 0.4%, binder accounts for 4%, thickener accounts for 0.5%, and wetting agent accounts for 0.1%).

[0151] The mixed slurry was evenly coated on the PE base film by micro-gravure roller coating, with a coating thickness of 3um. After heating at 200℃ for 1h, the thermal shrinkage ratio of the diaphragm was TD<2.7 and MD<2.9. The lithium ion conductivity was 1.25mS / cm, and the film breaking temperature was 207℃.

[0152] Example 5 :

[0153] Except that the lithium sulfonate group in the modified COFs material is replaced by the phenolic hydroxyl lithium group (modified COFs-2), the rest is the same as Example 1. The mass ratio of ceramic to modified COFs-2 material is 45%:55%. The solid and additive account for 95% and 5% respectively (dispersant accounts for 0.4%, binder accounts for 4%, thickener accounts for 0.5%, and wetting agent accounts for 0.1%).

[0154] The mixed slurry was evenly coated on the PE base film by micro-gravure roller coating, with a coating thickness of 3um. After heating at 200℃ for 1h, the thermal shrinkage ratio of the diaphragm was TD<2.8 and MD<3.0. The lithium ion conductivity was 1.17mS / cm, and the film breaking temperature was 207℃.

[0155] Comparative Example 1 :

[0156] The ceramic particles were evenly dispersed in water, with the mass ratio of ceramic and modified COFs materials being 100%:0%, and the solid and additive ratios being 95% and 5% respectively (dispersant 0.4%, binder 4%, thickener 0.5%, wetting agent 0.1%). The mixed slurry was evenly coated on the PE base film by micro-gravure roller coating, with a coating thickness of 3um. The membrane was broken after heating at 200℃ for 1h. The lithium ion conductivity was 0.72mS / cm, and the membrane breaking temperature was 156℃.

[0157] Comparative Example 2 :

[0158] The modified COFs material was dispersed in water, with the mass ratio of ceramic to modified COF being 0%:100%, and the solid and additive ratios being 95% and 5% respectively (dispersant 0.4%, binder 4%, thickener 0.5%, wetting agent 0.1%). The mixed slurry was evenly coated on the PE base film by micro-gravure roller coating, with a coating thickness of 3um. The membrane was broken after heating at 200℃ for 1h. The lithium ion conductivity was 0.059mS / cm, and the membrane breaking temperature was 152℃.

[0159] Comparative Example 3 :

[0160] Except for replacing the modified COFs material with a sulfonic acid group but unlithiated COFs (modified COFs-3) material, the rest is the same as Example 1. The mass ratio of ceramic and modified COFs-3 materials is 45%:55%. The solid and additive account for 95 and 5% respectively (dispersant accounts for 0.4%, binder accounts for 4%, thickener accounts for 0.5%, and wetting agent accounts for 0.1%). The mixed slurry is evenly coated on the PE base film by micro-gravure roller coating with a coating thickness of 3um. Heated at 200℃ for 1h, the thermal shrinkage ratio of the diaphragm TD<2.7, MD<2.9. The lithium ion conductivity is 1.03mS / cm, and the membrane rupture temperature is 200℃.

[0161] Comparative Example 4 :

[0162] Except that the modified COFs material is replaced by the COFs material without the lithium sulfonate group, the rest is the same as Example 1. The mass ratio of ceramic and modified COFs material is 45%:55%. The solid and additive account for 95 and 5% respectively (dispersant accounts for 0.4%, binder accounts for 4%, thickener accounts for 0.5%, wetting agent accounts for 0.1%). The mixed slurry is evenly coated on the PE base film by micro-gravure roller coating with a coating thickness of 3um. Heated at 200℃ for 1h, the thermal shrinkage ratio of the diaphragm TD<2.6, MD<2.8. The lithium ion conductivity is 0.053mS / cm, and the membrane rupture temperature is 200℃.

[0163] Comparative Example 5 :

[0164] Except for replacing the modified COFs material with MOF-5 material, the rest is the same as Example 1; the mass ratio of ceramic and MOF-5 material is 45%:55%. The solid and additive account for 95 and 5% respectively (dispersant accounts for 0.4%, binder accounts for 4%, thickener accounts for 0.5%, wetting agent accounts for 0.1%). The mixed slurry is evenly coated on the PE base film by micro-gravure roller coating, and the coating thickness is 3um. Heated at 200℃ for 1h, the thermal shrinkage ratio of the diaphragm TD<2.8, MD<3.0. The lithium ion conductivity is 0.045mS / cm, and the membrane rupture temperature is 204℃.

[0165] Comparative Example 6 :

[0166] Except that the modified COFs material is replaced by ZIF-67 material, the rest is the same as Example 1; the mass ratio of ceramic and ZIF-67 material is 45%:55%. The solid and additive account for 95 and 5% respectively (dispersant accounts for 0.4%, binder accounts for 4%, thickener accounts for 0.5%, and wetting agent accounts for 0.1%). The mixed slurry is evenly coated on the PE base film by micro-gravure roller coating, and the coating thickness is 3um. Heated at 200℃ for 1h, the thermal shrinkage ratio of the diaphragm TD<2.8, MD<3.0. The lithium ion conductivity is 0.032mS / cm, and the membrane rupture temperature is 203℃.

[0167] The following Tables 1 and 2 respectively give the composition and performance test data of the above-mentioned embodiment and comparative example.

[0168] Table 1:

[0169]

[0170] Table 2:

[0171]

[0172] It should be noted that, although the technical solution of the present invention is introduced with specific examples, those skilled in the art will appreciate that the present disclosure should not be limited thereto.

[0173] The embodiments of the present disclosure have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A composite separator for a secondary battery, characterized in that: The composite diaphragm comprises: A substrate layer, and a modified layer formed on at least one surface of the substrate layer; in, The substrate layer includes a polymer material; The modified layer includes modified covalent organic framework materials and inorganic particles. The modified covalent organic framework material has a group containing active hydrogen in its molecular structure. The hydrogen ions in the groups containing active hydrogen can be replaced by lithium ions, and at least part of the hydrogen ions in the groups containing active hydrogen are replaced by lithium ions.

2. The diaphragm according to claim 1, characterized in that The modified layers are present on both surfaces of the substrate layer, and the two modified layers are the same or different.

3. The diaphragm according to claim 1 or 2, characterized in that: The substrate layer includes a polyolefin resin; and the thickness of the modified layer is less than 5 μm.

4. The diaphragm according to any one of claims 1 to 3, characterized in that: The substrate layer is a porous resin film layer.

5. The diaphragm according to any one of claims 1 to 4, characterized in that: In the modified layer, the mass ratio of the modified covalent organic framework material to the inorganic particles is 3:7 to 7:

3.

6. The diaphragm according to any one of claims 1 to 5, characterized in that: The active hydrogen-containing groups include one or more of carboxyl groups, phosphoric acid groups, sulfonic acid groups, and phenolic hydroxyl groups.

7. The diaphragm according to any one of claims 1 to 6, characterized in that: The hydrogen ions in the active hydrogen-containing groups are substantially all replaced by lithium ions.

8. A method for preparing a diaphragm according to any one of claims 1 to 7, characterized in that: The method comprises: A step of modifying the covalent organic framework material to impart active hydrogen-containing groups to the molecules of the covalent organic framework material, and then causing the hydrogen ions in the active hydrogen-containing groups to be at least partially replaced by lithium ions to obtain the modified covalent organic framework material; A mixing step of dispersing and mixing the modified covalent organic framework material and the inorganic particles in water to obtain a mixed slurry; The step of forming the modified layer comprises applying the mixed slurry to at least one surface of the substrate layer.

9. The method according to claim 8, characterized in that In the mixing step, the dispersion mixing is carried out in the presence of a binder, and optionally, an auxiliary agent is added during the dispersion mixing process.

10. The method according to claim 8 or 9, characterized in that: In the step of forming the modified layer, the coating includes roller coating, blade coating, spot coating or spray coating.

Citation Information

Patent Citations

  • Sulfonic acid group-containing covalent organic framework / aluminum oxide composite material as well as preparation method and application thereof

    CN116715862A

  • High-safety diaphragm and electrochemical device comprising same

    CN118738762A

  • Covalent organic framework membranes, methods and uses thereof

    WO2023009072A2